Heterogeneous Raney Nickel and Cobalt Catalysts for Racemization and Dynamic Kinetic Resolution of Amines - Parvulescu, Andrei N.; Jacobs, Pierre A.; De Vos, Dirk E. (Advanced synthesis & catalysis, 2008)
Raney metals were studied as heterogeneous catalysts for racemization and dynamic kinetic resolution (DKR) of chiral amines, as an alternative to metals like palladium or ruthenium. Both Raney nickel and cobalt were able to selectively racemize various chiral amines with high selectivity. In the racemization of benzylic primary amines, the minor formation of side products, e.g., secondary amines, can be suppressed by varying the hydrogen pressure. In the racemization of aliphatic amines over Raney catalysts, the selectivity is very high, with the enantiomeric amine as the sole product. DKR of racemic aliphatic amines can be performed with immobilized Candida antarctica lipase B and Raney nickel in one pot; for 2‐hexylamine, a yield of 95 % of the acetylated amide was achieved, with 97 % ee. Attention is devoted to the compatibility of the enzyme and the metal catalyst during the DKR. For benzylic primary amines, a two‐pot process is proposed in which the liquid is alternatingly shuttled between two vessels containing the solid racemization catalyst and the biocatalyst. After 4 such cycles, the amide of (R)‐1‐phenylethylamine was obtained with 94 % yield and more than 90 % ee.